TRADITION DRAGON BOAT RACE ON SOCIETY TIONGHOA AT TANJUNGPINANG CITY KEPULAUAN RIAU - Vriska Revenlia; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tradition is a relic of the ancestors in order to preserve hereditary heritage, in every celebration of tradition has a history so that tradition is carried out every year. Here the author took the Dragon Boat Race Tradition is a tradition of ancestral ancestors of ethnic Chinese people who came from China, the many ethnic Chinese people who entered in the city of Tanjungpinang Riau Islands caused the tradition of Dragon Boat Race starting from 2003 held in Tanjungpinang City and made an annual event of Tanjungpinang . The Tradition which was originally the Sea Sanctuary which was held on the 5th of the 5th month according to the Chinese calendar, the activity was performed to commemorate the death of Qu Yuan which was a single minister at the time of the former empire did not commit mass corruption and the event activity has several stages. The results show that the implementation of the event through several stages: (1) The making of the canoe and the head of the canoe. (2) The prayer of the head of the boat (3) The calling of the loya (4) Eye coloring (5) The drum rhythm. But the stage has faded and not implemented again since the tradition of Dragon Boat Race turned into an event held in the city of Tanjungpinang. The author takes Social Change theory from Sztompka. In the theory of change telling the factors that cause change, one of the factors that cause changes in this tradition is increasing and decreasing the number of residents, a very prominent change is on the religious side.Keywords : Tradition, Dragon Boat Race, Tionghoa